PENTINGNYA STUDI RELEVAN DALAM MENYUSUN STRATEGI MANAJEMEN PENDIDIKAN YANG EFEKTIF - Putri, Loly Nadila; Muspawi, Mohamad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Education management covers various aspects, ranging from the management of human resources, curriculum, facilities, to education policy. This literature review aims to explore the importance of Relevant Studies in developing effective education management strategies. Based on the literature review and previous research, in an increasingly complex and dynamic era, developing an effective education management strategy is a challenge for education stakeholders. One of the important elements in the strategy development process is the utilization of relevant studies as an empirical and theoretical basis. The research method used is a literature study by collecting and analyzing articles, journals and books related to the importance of Relevant Studies in developing effective education management strategies. The results of the literature review show that Relevant Studies play an important role in developing an effective, sustainable and adaptive education management strategy to the challenges of the times. Therefore, it is important for educational institutions, governments and all stakeholders to actively support and integrate the results of relevant studies into every aspect of education management, in order to create a better education that is in line with future challenges.